2012
DOI: 10.3390/en5114340
|View full text |Cite
|
Sign up to set email alerts
|

Design and Fabrication of a Novel Hybrid-Structure Heat Pipe for a Concentrator Photovoltaic

Abstract: This study presents a design method to fabricate a novel hybrid-structure flat plate heat pipe (NHSP heat pipe) for a concentrator photovoltaic. The NHSP heat pipe is composed of a flattened copper pipe and a sintered wick structure, and a coronary-stent-like rhombic copper mesh supports the structure. The coronary-stent-like supporting structure enhances the mechanical strength and shortens the reflux path of the working fluid. Experiments demonstrate that the sintered capillary heat pipe reduces the thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…In yet another study, a hybrid‐structured flat copper heat pipe with sintered wick supported by coronary‐stent‐like mesh was designed and analyzed through experiment. The results revealed a reduction of 65% in total thermal resistance and an increase of 3.1% electrical efficiency of CPV . Liquid immersion cooling was used to study the performance of the silicon solar cell under a concentration of 10 to 30 Suns and the results showed an increase in the cell efficiency by 8.5% to 15.2% …”
Section: Introductionmentioning
confidence: 98%
“…In yet another study, a hybrid‐structured flat copper heat pipe with sintered wick supported by coronary‐stent‐like mesh was designed and analyzed through experiment. The results revealed a reduction of 65% in total thermal resistance and an increase of 3.1% electrical efficiency of CPV . Liquid immersion cooling was used to study the performance of the silicon solar cell under a concentration of 10 to 30 Suns and the results showed an increase in the cell efficiency by 8.5% to 15.2% …”
Section: Introductionmentioning
confidence: 98%
“…In CPV‐PCM systems, the choice of coolant is less constrained because there is less need for heat storage. Huang et al fabricated a hybrid heat pipe structure with pure water as working fluid for HCPV. Xu et al designed a microchannel cooling method with silicon channels and water for working fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Peigné et al [3] designed a system to heat a low-energy building by coupling a heat-recovery ventilation system with a three-fluid heat exchanger located on the chimney of a wood-pellet stove and their case study results showed that heat transfer rates can be predicted with a relative difference lower than 5%. A study by Huang et al [4] fabricated a novel hybrid-structure flat plate heat pipe for a concentrator photovoltaic system and the results indicated that it can reduce thermal resistance by 65% after a supporting structure is added to the heat pipe.…”
Section: Introductionmentioning
confidence: 99%